Light-Fenton catalytic material, preparation method and application thereof and method for degrading antibiotic wastewater

By introducing the composite structure of the Fe2O3 quantum dot-supported g-C3N4 and TiO2 nanowire array in the photo-Fenton catalyst, the existing photo-Fenton catalyst has been solved in the narrow photoresponse range, low catalytic efficiency, narrow pH range and preparation of the existing photoresponse range, and low catalytic efficiency, narrow pH range and The complex process problem has achieved more efficient, stable and economical antibiotic wastewater degradation effect.

CN119430455AInactive Publication Date: 2025-02-14LIAONING ZHONGKE NANOMATERIALS DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411981835.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing light-Fenton catalysts have shortcomings in the problems of narrow photo response range, low catalytic efficiency, narrow pH range, complex preparation process and high cost.

Method used

The photo-Fenton catalytic material composed of TiO2 nanowire array, modified carbon nitride and Fe2O3 quantum dots is used to load the g-C3N4 surface by Fe2O3 quantum dots to enhance its visible light response capability and is compounded with the TiO2 nanowire array. Form a heterojunction structure to improve catalytic efficiency.

Benefits of technology

The photoresponse range is expanded, the degradation efficiency and stability is improved, the wider pH range is adapted, and the preparation process is simplified, reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the field of photocatalytic technology and emerging pollutant degradation, in particular to a light-Fenton catalytic material, a preparation method and application thereof and a method for degrading antibiotic wastewater. The light-Fenton catalytic material provided by the invention is stable in structure, and a Fe2O3 quantum dot loaded g-C3N4 and TiO2 nanowire composite structure is adopted, so that the response range to visible light is effectively expanded, and the degradation efficiency is effectively improved. In addition, the photo-Fenton catalytic material provided by the invention forms a stable heterojunction structure, so that the separation efficiency of photo-induced electrons and holes in the material is improved, the recombination rate is remarkably reduced, and the generation rate of free radicals is improved. The photo-Fenton catalytic material provided by the invention can maintain efficient catalytic activity in a wide range of pH value of 2-9, and breaks through the harsh demand of a traditional Fenton catalytic material on an acid environment. The light-Fenton catalytic material provided by the invention is simple in preparation process, mild in reaction condition and low in production cost, and has high practical application feasibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalytic technology and emerging pollutant degradation, in particular to a photo-Fenton catalytic material, a preparation method and application thereof, and a method for degrading antibiotic wastewater. Background Art

[0002] In recent years, the widespread use and abuse of antibiotics has led to increasingly serious antibiotic pollution in water bodies. Antibiotic residues not only damage the aquatic ecosystem, but may also enter the human body through drinking water or aquatic food chains, posing a threat to health. Traditional antibiotic wastewater treatment methods mainly include physical treatment methods (such as adsorption, coagulation, sedimentation, etc.), biodegradation methods (such as aerobic and anaerobic biodegradation methods) and advanced oxidation processes (AOPs).

[0003] Physical treatment methods are low-cost, but it is difficult to effectively remove high-concentration pollutants; biodegradation methods are relatively green and environmentally friendly, but the treatment speed is slow and the efficiency is low. Advanced oxidation processes degrade organic pollutants by generating active oxides (such as ·OH radicals), but the single photocatalytic method is not ideal in the degradation of antibiotic wastewater. Therefore, the photo-Fenton catalytic method that combines photocatalysis and Fenton reaction has become a new and efficient solution. This method can not only enhance the efficiency of photocatalytic degradation, but also generate more ·OH radicals under the combined action of light and oxidants, thereby achieving more efficient antibiotic wastewater treatment.

[0004] In the existing photo-Fenton catalyst technology solutions, TiO2, Fe2O3, etc. are usually used as the main active ingredients. For example, in research, TiO2 is widely used in photocatalytic degradation of pollutants, which has excellent chemical stability and high ultraviolet light responsiveness. However, TiO2 has a low response ability to visible light, which limits its application range. In order to solve this problem, the introduction of Fe2O3 quantum dots has become an effective method. Fe2O3 quantum dots can enhance the visible light response range of TiO2 and promote the separation of photogenerated electron-hole pairs.

[0005] Based on the photo-Fenton catalytic technology, there are currently the following problems:

[0006] (1) Narrow light response range and low catalytic efficiency. Although TiO2 used in the prior art has good photocatalytic performance, it is mainly active in the ultraviolet light region and has poor response to visible light, resulting in low photocatalytic efficiency under daily lighting conditions. Although the composite material of carbon nitride (g-C3N4) and TiO2 has a certain visible light response ability, its photogenerated electron and hole separation effect is limited, affecting the overall catalytic efficiency.

[0007] (2) High recombination rate of photogenerated electrons and holes, resulting in low catalytic efficiency. In traditional photocatalyst systems, due to the lack of an effective electron-hole separation mechanism, photogenerated electrons and holes are easily recombined, resulting in low efficiency of free radical generation, which limits the rate and efficiency of the photocatalytic reaction. For example, traditional TiO2 and Fe2O3 composites achieve photocatalytic degradation of pollutants by loading Fe2O3 particles on a TiO2 matrix and utilizing the photogenerated electrons and holes generated by them. However, the photocatalytic efficiency of this combination is still limited, especially in the absence of an efficient interface carrier separation mechanism, the synergistic effect between Fe2O3 and TiO2 is difficult to fully exert. In recent years, researchers have tried to composite g-C3N4 with Fe2O3 or TiO2 to enhance the catalyst's absorption capacity for visible light and photocatalytic activity. The porous structure of g-C3N4 can increase the specific surface area and provide more active sites for the adsorption and reaction of pollutants. However, the photogenerated electron-hole separation effect of this type of composite material is still limited, and the catalytic efficiency needs to be improved.

[0008] (3) The application pH range is narrow and the universality is poor. Traditional Fenton catalysts mostly work under acidic conditions with a pH value of 3. The narrow pH range limits the application of catalysts in neutral or alkaline environments. In actual wastewater treatment, it is difficult to adjust to an ideal acidic environment, which increases the operating cost and difficulty.

[0009] (4) The preparation process is complex and the cost is high. For example, existing TiO2 and g-C3N4 composite materials are usually prepared through complex processes such as multi-step chemical deposition or high-temperature calcination, which not only increases the complexity and cost of production, but also affects the practical application and promotion of the materials. In addition, the chemical reagents or solvents used in some processes are not environmentally friendly, and the preparation process may pollute the environment. Summary of the invention

[0010] In view of this, the technical problem to be solved by the present invention is to provide a photo-Fenton catalytic material, a preparation method and application thereof, and a method for degrading antibiotic wastewater. The photo-Fenton catalytic material provided by the present invention has a wide light response range, high degradation efficiency and degradation stability, a wide pH adaptability range, and a simple preparation process.

[0011] The present invention provides a photo-Fenton catalytic material, which is obtained from the following components:

[0012] A carbon substrate having a TiO2 nanowire array disposed thereon;

[0013] Modified carbon nitride, the modified carbon nitride comprises carbon nitride and Fe2O3 quantum dots supported on the carbon nitride.

[0014] The carbon nitride in the modified carbon nitride described in the present invention is graphite phase carbon nitride (g-C3N4), and the carbon nitride is preferably porous carbon nitride, which can make the obtained modified carbon nitride have a porous structure, so that the modified carbon nitride has a larger specific surface area and more reactive sites, so as to better undergo redox reactions with pollutants, thereby improving the degradation efficiency.

[0015] The introduction of Fe2O3 quantum dots in the present invention enhances the visible light response range of g-C3N4, inhibits the recombination of photogenerated electrons and holes, and at the same time, the photogenerated electrons can promote the Fe 3+ / Fe 2+ The redox cycle between the two is induced by ·OH, thereby achieving the purpose of efficiently degrading antibiotic wastewater. The mass percentage of the Fe2O3 quantum dots on the carbon nitride of the present invention is 1 wt% to 9 wt%, preferably 5 wt% to 7 wt%, and more preferably 5 wt%.

[0016] The carbon substrate of the present invention is graphite felt, carbon cloth or activated carbon, preferably graphite felt. The carbon substrate of the present invention is used to support the growth of TiO2.

[0017] The photo-Fenton catalytic material provided by the present invention uses carbon material as a substrate, loads g-C3N4 through Fe2O3 quantum dots, enhances the response range of g-C3N4 to visible light, and composites it with a TiO2 nanowire array grown on a carbon substrate, utilizing the photocatalytic properties of the TiO2 nanowires. The Fe2O3 quantum dots, g-C3N4 and TiO2 nanowire arrays form a heterojunction structure, so that the photo-Fenton catalytic material can respond to a wider spectral range, especially enhance the response to visible light, so that the photo-Fenton catalytic material of the present invention has a higher catalytic activity under natural light sources. Therefore, the photo-Fenton catalytic material of the present invention, as a photo-Fenton catalyst, overcomes the problem that the traditional TiO2 photocatalyst mainly absorbs ultraviolet light, resulting in poor catalytic effect under daily visible light irradiation.

[0018] The heterojunction structure of the photo-Fenton catalytic material of the present invention also improves the separation efficiency of photogenerated electrons and holes, reduces the recombination probability, realizes stable electron-hole separation, increases the lifetime of photogenerated carriers, significantly improves the photo-Fenton reaction efficiency and overall catalytic activity of the catalyst, and overcomes the problem that photogenerated electrons and holes are prone to recombination in traditional photocatalysts, resulting in a low generation rate of active free radicals. In addition, the heterojunction structure of the photo-Fenton catalytic material of the present invention also enhances the generation efficiency of ·OH through the reduction-oxidation cycle process of Fe2O3 quantum dots, so that the degradation rate of the photo-Fenton catalytic material of the present invention in the photo-Fenton reaction is much higher than that of a traditional single photocatalyst.

[0019] In addition, the light-Fenton catalytic material of the present invention has a stable structure and can maintain catalytic activity for a long time and multiple uses, reducing the frequency of material replacement and improving the overall economy. The reusability of the catalyst is an important factor affecting practical applications. Through the stability of the heterojunction structure and the synergistic effect between materials, the catalyst of the present invention can still maintain an efficient catalytic effect after multiple reaction cycles, showing good cycle stability and durability. This feature ensures the long-term application value of the catalyst in actual wastewater treatment.

[0020] The photo-Fenton catalytic material provided by the present invention maintains efficient catalytic activity within the pH range of 2 to 9, breaking through the pH limit of the traditional Fenton reaction and enabling its application in a wider range of wastewater treatment environments; and the catalyst has a stable structure, can maintain efficient activity during multiple uses, has good cyclic stability, and is suitable for long-term application in actual wastewater treatment.

[0021] The present invention also provides a method for preparing the photo-Fenton catalytic material described in any of the above technical solutions, comprising the following steps: subjecting a carbon substrate provided with a TiO2 nanowire array to a deposition reaction in a modified carbon nitride solution to obtain a photo-Fenton catalytic material.

[0022] The deposition reaction of the present invention includes electrophoretic deposition, electrostatic spraying or ion exchange deposition. Preferably, the present invention electrophoretically deposits a carbon substrate provided with a TiO2 nanowire array in an acetone solution of modified carbon nitride under the action of iodine. Electrophoretic deposition is a technical method for depositing charged particles onto a conductive substrate under the action of an electric field, which is used to form a composite catalyst; specifically, iodine and modified carbon nitride are ultrasonicated in acetone, and then the carbon substrate provided with a TiO2 nanowire array is electrophoretically deposited in the resulting solution, and then the resulting material is cured in an oven to obtain a light-Fenton catalytic material. The dosage ratio of iodine, modified carbon nitride and acetone of the present invention is: (18~22) mg: (8~12) mg: (25~35) mL, preferably 20 mg: 10 mg: 30 mL. The ultrasonic time of the present invention is 10 min~20 min, preferably 15 min. The deposition reaction of the present invention can load Fe2O3 quantum dots onto g-C3N4 composite materials, that is, the modified carbon nitride is evenly distributed on a carbon substrate provided with a TiO2 nanowire array to form a heterojunction, which can expand visible light absorption. The heterojunction between the two components is conducive to carrier separation and enhances the stability and catalytic performance of the material.

[0023] The modified carbon nitride of the present invention is obtained by loading Fe2O3 quantum dots into g-C3N4, and is specifically prepared by the following method: carbon nitride, FeCl3·6H2O and NH4HCO3 are mixed and stirred for 10 h to 14 h, and the material obtained after the mixing and stirring is calcined at 340° C. to 360° C. for 1.5 h to 2.5 h to obtain the modified carbon nitride. More specifically, carbon nitride is dispersed in a solvent by ultrasonication to obtain a carbon nitride suspension, FeCl3·6H2O and NH4HCO3 are added to the carbon nitride suspension and ultrasonically mixed and stirred at room temperature for 10 h to 14 h, preferably 12 h, the material obtained after ultrasonic mixing and stirring is centrifuged, washed, and dried, the dried material is ground and calcined at 340°C to 360°C for 1.5 h to 2.5 h, with a temperature gradient of 4°C / min to 6°C / min, preferably calcined at 350°C for 2 h, with a temperature gradient of 5°C / min, and the calcined material is dried to obtain modified carbon nitride. The drying described in the present invention is vacuum drying. The method of loading Fe2O3 quantum dots into g-C3N4 in the present invention realizes uniform loading of quantum dots, which helps to form a stable heterojunction structure.

[0024] The carbon nitride used in the process of preparing the modified carbon nitride of the present invention is porous carbon nitride, which is prepared by supramolecular self-assembly of melamine and cyanuric acid. Supramolecular self-assembly is a spontaneous process of forming a stable structure through non-covalent bonds (such as hydrogen bonds, van der Waals forces, etc.); the porous carbon nitride is prepared by the following method: melamine and cyanuric acid in a mass ratio of 1: (1-1.2) are stirred in a solvent for 10 h-14 h, filtered to obtain a precipitate after standing, and the precipitate is calcined at 500° C.-550° C. for 3 h-5 h to obtain the porous carbon nitride. More specifically, melamine and cyanuric acid in a mass ratio of 1: (1-1.2) are stirred in a solvent for 10-14 h to perform a supramolecular self-assembly reaction to form a porous carbon nitride structure, and then the structure is allowed to stand and filtered to obtain a precipitate. The precipitate is dried and calcined at 500-550°C for 3-5 h with a temperature increase gradient of 2-3°C / min, preferably 2.5°C / min, to obtain porous carbon nitride.

[0025] The carbon substrate provided with a TiO2 nanowire array according to the present invention is prepared by a hydrothermal method, specifically prepared by the following method: placing the carbon substrate in a mixed solution of concentrated hydrochloric acid, tetrabutyl titanate and water and drying it at 140°C to 160°C for 18h to 22h to obtain a carbon substrate provided with a TiO2 nanowire array. More specifically, tetrabutyl titanate is slowly added to the concentrated hydrochloric acid while stirring, and then water is added thereto and continued to stir, and then the carbon substrate is placed in the resulting solution, and dried at 140°C to 160°C for 18h to 22h, preferably at 150°C for 20h, to obtain a carbon substrate provided with a TiO2 nanowire array. The ratio of the amount of concentrated hydrochloric acid, tetrabutyl titanate and water according to the present invention is: (8~12) mL: (0.22~0.28) mL: (8~12) mL, preferably: 10mL: 0.25mL: 10 mL. The carbon substrate according to the present invention is the same as above and will not be repeated.

[0026] The preparation method of the photo-Fenton catalytic material provided by the present invention adopts easy-to-operate and environmentally friendly preparation processes such as supramolecular self-assembly, hydrothermal method and electrophoretic deposition, which significantly reduces the preparation steps and reduces the production cost. Compared with the multi-step deposition and high-temperature calcination in the traditional method, the preparation process of the present invention is simple to operate, and the required raw materials are environmentally friendly and easy to obtain, and the energy consumption of the entire preparation process is low. This improvement reduces the production cost, is suitable for large-scale production, and is convenient for industrial promotion and practical application.

[0027] The present invention also provides the use of the photo-Fenton catalytic material described in any of the above technical solutions or the photo-Fenton catalytic material obtained by the preparation method described in any of the above technical solutions in the preparation of antibiotic wastewater degradation agents. The mechanism of the photo-Fenton catalytic material described in the present invention for degrading antibiotic wastewater is as follows: Fe2O3 quantum dots are loaded on the surface of g-C3N4, which can enhance the visible light absorption performance of the material. Under visible light irradiation, g-C3N4 absorbs light energy to generate photogenerated electrons and holes. The heterojunction formed by Fe2O3 quantum dots and g-C3N4 can effectively separate electrons and holes, inhibit recombination, and enhance the redox ability of the catalyst. Electrons are transferred from g-C3N4 to Fe2O3, thereby promoting Fe 3+ / Fe 2+ The redox cycle generates hydroxyl radicals (·OH) on the catalyst surface. With the assistance of TiO2 nanowires, more ·OH radicals are generated, accelerating the degradation reaction of pollutants.

[0028] Specifically, the present invention provides a method for degrading antibiotic wastewater, comprising the following steps:

[0029] S1) adsorbing an antibiotic wastewater degradation agent in antibiotic wastewater in the absence of light to obtain dark-field adsorbed wastewater; the antibiotic wastewater degradation agent is the photo-Fenton catalytic material described in any of the above technical solutions or the photo-Fenton catalytic material obtained by the preparation method described in any of the above technical solutions;

[0030] S2) Under light conditions, the oxidant is reacted with the dark field adsorption wastewater obtained in step S1).

[0031] The present invention firstly adsorbs the antibiotic wastewater degradation agent in the antibiotic wastewater under lightless conditions to obtain dark field adsorbed wastewater. The concentration of the antibiotic wastewater of the present invention is 10mg / L~50mg / L; the dosage of the antibiotic wastewater degradation agent is 0.1g / L~1g / L, preferably 0.2g / L. The adsorption time of the present invention is 100min~140min, preferably 120min. The antibiotic wastewater of the present invention is a water waste containing antibiotic components. Due to the strong stability of antibiotics, it is difficult to degrade by traditional methods. The light-Fenton catalytic material of the present invention can be used as an antibiotic wastewater degradation agent to efficiently treat such wastewater. The main component of the antibiotic wastewater of the present invention is tetracycline hydrochloride (TC).

[0032] Before the antibiotic wastewater degradation agent is adsorbed in the antibiotic wastewater, the pH of the antibiotic wastewater needs to be adjusted to 2-9, preferably 3-9, and more preferably 3. The wastewater pH adjustment in the present invention can be adjusted by dilute hydrochloric acid and dilute sodium hydroxide, but other acidic and alkaline substances can also be considered for pH control (such as phosphoric acid, sulfuric acid, ammonia water, etc.), thereby increasing the adaptability of the catalyst in different water quality environments.

[0033] The light-Fenton catalytic material of the present invention can maintain efficient catalytic activity in a wide range of pH 2 to 9, breaking through the limitations of the traditional Fenton reaction in terms of pH value, so that it also has excellent antibiotic wastewater degradation effect in a neutral to alkaline environment. The traditional Fenton reaction has strict requirements on acidic conditions, and usually requires an environment of pH=3 to ensure reaction efficiency, and this condition is difficult to control in actual wastewater treatment. The high efficiency of the light-Fenton catalytic material of the present invention in a wide pH range is due to its material structure and composite design, which not only reduces the dependence on acidic conditions, but also allows antibiotic wastewater to be effectively degraded under near-neutral conditions. This adaptability gives it a great advantage in actual wastewater treatment applications.

[0034] After the dark field adsorption wastewater is obtained, the oxidant and the obtained dark field adsorption wastewater are reacted under illumination conditions. Specifically, 0.1mM~0.5mM oxidant solution is added to the dark field adsorption wastewater, preferably 0.3mM oxidant solution is added, under simulated sunlight irradiation, and a 420nm filter is used to remove the ultraviolet light part, and a photo-Fenton reaction is carried out for 30min~120min, that is, the treatment of the antibiotic wastewater is completed. The oxidant of the present invention is selected from one or more of H2O2, persulfate or ozone. By selecting a variety of oxidants, a wider range of oxidative degradation effects can be achieved. These oxidants can also generate free radicals under illumination conditions to achieve the purpose of efficiently degrading antibiotic wastewater.

[0035] The present invention provides a photo-Fenton catalytic material, a preparation method and application thereof, and a method for degrading antibiotic wastewater. The photo-Fenton catalytic material provided by the present invention adopts a composite structure of g-C3N4 and TiO2 nanowires loaded with Fe2O3 quantum dots. The introduction of Fe2O3 quantum dots enhances the visible light response of g-C3N4, and the presence of TiO2 nanowires further enhances the light absorption rate and reaction effect, effectively expands the response range of the catalyst to visible light, and significantly improves the degradation efficiency of the catalyst under daily lighting conditions. In addition, the Fe2O3 quantum dots form a stable heterojunction structure with g-C3N4 and TiO2 nanowires, which improves the separation efficiency of photogenerated electrons and holes inside the material, significantly reduces the recombination rate, and increases the generation rate of free radicals, thereby accelerating the photo-Fenton catalytic reaction speed; in addition, its structure is stable, and the catalytic activity can be maintained for a long time and multiple uses, reducing the frequency of material replacement and improving the overall economy. The photo-Fenton catalytic material provided by the present invention can maintain high catalytic activity in a wide range of pH values ​​from 2 to 9, so that it can be used in a wider range of wastewater treatment scenarios, and is particularly suitable for antibiotic wastewater treatment scenarios where pH conditions are difficult to strictly control. The preparation process of the photo-Fenton catalytic material provided by the present invention uses simple and easy process routes such as supramolecular self-assembly, hydrothermal method and electrophoretic deposition to prepare the photo-Fenton catalytic material. The preparation process has fewer steps, a simple process, mild reaction conditions, and the reagents used are environmentally friendly and easy to obtain, thereby significantly reducing production costs and improving the practical application feasibility of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 XRD patterns of the photo-Fenton catalysts prepared in Examples 1 to 5 of the present invention;

[0037] Figure 2 This is a SEM photo of the 1%-FCN / TiO2 photo-Fenton catalyst prepared in Example 1 of the present invention;

[0038] Figure 3This is a SEM photo of the 3%-FCN / TiO2 photo-Fenton catalyst prepared in Example 2 of the present invention;

[0039] Figure 4 This is a SEM photo of the 5%-FCN / TiO2 photo-Fenton catalyst prepared in Example 3 of the present invention;

[0040] Figure 5 This is a SEM photo of the 7%-FCN / TiO2 photo-Fenton catalyst prepared in Example 4 of the present invention;

[0041] Figure 6 This is a SEM photo of the 9%-FCN / TiO2 photo-Fenton catalyst prepared in Example 5 of the present invention;

[0042] Figure 7 This is a SEM photo of smooth graphite felt;

[0043] Figure 8 FTIR images of the photo-Fenton catalysts prepared in Examples 1 to 5 of the present invention;

[0044] Fig. 9 The degradation rate-time curve of tetracycline hydrochloride degradation under visible light by the photo-Fenton catalyst prepared in Examples 1 to 5 of the present invention;

[0045] Fig.10 The catalytic degradation diagram of 5%-FCN / TiO2 photo-Fenton catalyst prepared in Example 3 of the present invention to tetracycline hydrochloride solution at different pH values;

[0046] Fig.11 This is a graph showing the TC degradation efficiency of the 5%-FCN / TiO2 photo-Fenton catalyst prepared in Example 3 of the present invention for a tetracycline hydrochloride solution at different bias voltages. DETAILED DESCRIPTION

[0047] The present invention discloses a photo-Fenton catalytic material, a preparation method and application thereof, and a method for degrading antibiotic wastewater. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application of this article without departing from the content, spirit and scope of the present invention to realize and apply the technology of the present invention.

[0048] The present invention will be further described below in conjunction with embodiments:

[0049] Example 1

[0050] 1.2612 g of melamine and 1.2907 g of cyanuric acid were dissolved in 60 mL of deionized water and stirred for 12 h, dried at 80 °C, and the dried sample was calcined at 550 °C for 4 h in a muffle furnace with a temperature gradient of 2.3 °C / min. Powdered porous-CN was obtained. 1 g of the above sample was weighed and dissolved in a beaker containing 50 mL of ethanol, ultrasonicated at room temperature for 90 min, 0.01 g of FeCl3·6H2O and 0.237 g of NH4HCO3 were added thereto, stirred at room temperature for 12 h, the sample was centrifuged, washed, dried, calcined at 350 °C for 2 h in a muffle furnace with a temperature gradient of 5 °C / min, and a composite catalytic material was obtained after cooling, named 1%-FCN. 10 mL of concentrated hydrochloric acid was poured into a 50 mL reactor, 0.25 mL of tetrabutyl titanate was added dropwise, and then 10 mL of deionized water was added. After stirring for a certain period of time, the graphite felt was placed in it and dried at 150°C for 20 h. 20 mg of iodine and 10 mg of 1%-FCN powder were poured into 30 mL of acetone, ultrasonicated for 15 min, and the TiO2 nanoarray grown on the graphite felt was placed in the solution for electrophoretic deposition. Finally, the sample was placed in an oven for curing to obtain a 1%-FCN / TiO2 photo-Fenton catalyst.

[0051] Example 2

[0052] 1.2612g of melamine and 1.2907g of cyanuric acid were dissolved in 60mL of deionized water and stirred for 12h, dried at 80℃, and the dried sample was calcined at 550℃ in a muffle furnace for 4h with a temperature gradient of 2.3℃ / min. Powdered porous-CN was obtained. 1g of the above sample was weighed and dissolved in a beaker containing 50mL of ethanol, ultrasonicated at room temperature for 90min, 0.03g of FeCl3·6H2O and 0.237g of NH4HCO3 were added thereto, stirred at room temperature for 12h, the sample was centrifuged, washed, dried, calcined at 350℃ in a muffle furnace for 2h with a temperature gradient of 5℃ / min, and a composite catalytic material was obtained after cooling, named 3%-FCN. 10 mL of concentrated hydrochloric acid was poured into a 50 mL reactor, 0.25 mL of tetrabutyl titanate was added dropwise, and then 10 mL of deionized water was added. After stirring for a certain period of time, the graphite felt was placed in and dried at 150 ° C for 20 h. 20 mg of iodine and 10 mg of 3%-FCN powder were poured into 30 mL of acetone, ultrasonicated for 15 min, and the TiO2 nanoarray grown on the graphite felt was placed in the solution for electrophoretic deposition. Finally, the sample was placed in an oven for curing to obtain a 3%-FCN / TiO2 photo-Fenton catalyst.

[0053] Example 3

[0054] 1.2612g of melamine and 1.2907g of cyanuric acid were dissolved in 60mL of deionized water and stirred for 12h, dried at 80℃, and the dried sample was calcined at 550℃ in a muffle furnace for 4h with a temperature gradient of 2.3℃ / min. Powdered porous-CN was obtained. 1g of the above sample was weighed and dissolved in a beaker containing 50mL of ethanol, ultrasonicated at room temperature for 90min, 0.05g of FeCl3·6H2O and 0.237g of NH4HCO3 were added thereto, stirred at room temperature for 12h, the sample was centrifuged, washed, dried, calcined at 350℃ in a muffle furnace for 2h with a temperature gradient of 5℃ / min, and a composite catalytic material was obtained after cooling, named 5%-FCN. 10 mL of concentrated hydrochloric acid was poured into a 50 mL reactor, 0.25 mL of tetrabutyl titanate was added dropwise, and then 10 mL of deionized water was added. After stirring for a certain period of time, the graphite felt was placed in and dried at 150 ° C for 20 h. 20 mg of iodine and 10 mg of 5%-FCN powder were poured into 30 mL of acetone, ultrasonicated for 15 min, and the TiO2 nanoarray grown on the graphite felt was placed in the solution for electrophoretic deposition. Finally, the sample was placed in an oven for curing to obtain a 5%-FCN / TiO2 photo-Fenton catalyst.

[0055] Example 4

[0056] 1.2612g of melamine and 1.2907g of cyanuric acid were dissolved in 60mL of deionized water and stirred for 12h, dried at 80℃, and the dried sample was calcined at 550℃ in a muffle furnace for 4h with a temperature gradient of 2.3℃ / min. Powdered porous-CN was obtained. 1g of the above sample was weighed and dissolved in a beaker containing 50mL of ethanol, ultrasonicated at room temperature for 90min, 0.07g of FeCl3·6H2O and 0.237g of NH4HCO3 were added thereto, stirred at room temperature for 12h, the sample was centrifuged, washed, dried, calcined at 350℃ in a muffle furnace for 2h with a temperature gradient of 5℃ / min, and a composite catalytic material was obtained after cooling, named 7%-FCN. 10 mL of concentrated hydrochloric acid was poured into a 50 mL reactor, 0.25 mL of tetrabutyl titanate was added dropwise, and then 10 mL of deionized water was added. After stirring for a certain period of time, the graphite felt was placed in it and dried at 150 ° C for 20 h. 20 mg of iodine and 10 mg of 7%-FCN powder were poured into 30 mL of acetone, ultrasonicated for 15 min, and the TiO2 nanoarray grown on the graphite felt was placed in the solution for electrophoretic deposition. Finally, the sample was placed in an oven for curing to obtain a 7%-FCN / TiO2 photo-Fenton catalyst.

[0057] Example 5

[0058] 1.2612g of melamine and 1.2907g of cyanuric acid were dissolved in 60mL of deionized water and stirred for 12h, dried at 80℃, and the dried sample was calcined at 550℃ in a muffle furnace for 4h with a temperature gradient of 2.3℃ / min. Powdered porous-CN was obtained. 1g of the above sample was weighed and dissolved in a beaker containing 50mL of ethanol, ultrasonicated at room temperature for 90min, 0.09g of FeCl3·6H2O and 0.237g of NH4HCO3 were added thereto, stirred at room temperature for 12h, the sample was centrifuged, washed, dried, calcined at 350℃ in a muffle furnace for 2h with a temperature gradient of 5℃ / min, and a composite catalytic material was obtained after cooling, named 3%-FCN. 10 mL of concentrated hydrochloric acid was poured into a 50 mL reactor, 0.25 mL of tetrabutyl titanate was added dropwise, and then 10 mL of deionized water was added. After stirring for a certain period of time, the graphite felt was placed in it and dried at 150 ° C for 20 h. 20 mg of iodine and 10 mg of 9%-FCN powder were poured into 30 mL of acetone, ultrasonicated for 15 min, and the TiO2 nanoarray grown on the graphite felt was placed in the solution for electrophoretic deposition. Finally, the sample was placed in an oven for curing to obtain a 9%-FCN / TiO2 photo-Fenton catalyst.

[0059] like Figure 1 As shown, Figure 1 XRD diagram of the photo-Fenton catalyst prepared in Examples 1 to 5 of the present invention. It can be clearly seen from the figure that the synthesized pure g-C3N4 has two significant characteristic diffraction peaks, which are located at a wide and weak peak at 13.1° and a narrow and strong peak at 27.4°. The former belongs to the (001) crystal plane of the melon-like substance, and the latter belongs to the (002) crystal plane of the interlayer stacked aromatic structure. The simultaneous appearance of these two characteristic diffraction peaks confirms that the sample is a g-C3N4 structure. The synthesized TiO2 nanowires have four strong characteristic diffraction peaks at 27.45°, 36.0°, 41.2°, and 54.3°, corresponding to the (110), (101), (111), and (211) crystal planes of rutile titanium dioxide, respectively. The appearance of these strong diffraction peaks indicates that rutile titanium dioxide has been successfully synthesized. Titanium dioxide nanowires grow on a carbon cloth substrate. The characteristic diffraction peak of the carbon cloth is not obvious from the broad and weak peak at 13.1°. After compounding g-C3N4, it is difficult to distinguish the diffraction peak of the (001) crystal plane of melon-like substances. Combining the XRD diffraction peaks of g-C3N4 and TiO2, the synthesized g-C3N4 / TiO2 core-shell nanowires show the characteristic peak structure of both. The weak peak at 13.1° is broader due to the introduction of the matrix carbon cloth. At 27.4°, the (002) diffraction peak of g-C3N4 and the diffraction peak of the rutile (110) crystal plane are almost inseparable.

[0060] like Figure 2~Figure 7 As shown, Figure 2This is a SEM photo of the 1%-FCN / TiO2 photo-Fenton catalyst prepared in Example 1 of the present invention. Figure 3 This is a SEM photo of the 3%-FCN / TiO2 photo-Fenton catalyst prepared in Example 2 of the present invention. Figure 4 This is a SEM photo of the 5%-FCN / TiO2 photo-Fenton catalyst prepared in Example 3 of the present invention. Figure 5 This is a SEM photo of the 7%-FCN / TiO2 photo-Fenton catalyst prepared in Example 4 of the present invention. Figure 6 This is a SEM photo of the 9%-FCN / TiO2 photo-Fenton catalyst prepared in Example 5 of the present invention. Figure 7 This is a SEM photo of smooth graphite felt.

[0061] In order to study the degradation effect of a photo-Fenton catalyst prepared in accordance with an embodiment of the present invention on treating antibiotics in water by combining modified carbon nitride loaded with Fe2O3 quantum dots and TiO2 nanowires, the photo-Fenton catalyst prepared in accordance with an embodiment of the present invention was subjected to the following series of tests to prove:

[0062] Photo-Fenton degradation test: Prepare 100 mL of 20 mg / L tetracycline solution, weigh 10 mg of the photo-Fenton catalysts prepared in Regulations 1 to 5, which are the composites of modified carbon nitride and TiO2 nanowires loaded with Fe2O3 quantum dots. Add the catalysts to the tetracycline solution and place it in the reaction device.

[0063] Dark field adsorption was carried out under lightless conditions to reach adsorption equilibrium. The dark field adsorption time was 120 minutes. After the dark field adsorption was completed, the experimental xenon lamp was turned on, and the ultraviolet light part was removed with a 420nm filter. The reaction was continued with stirring for 120 minutes. Samples were taken every 30 minutes, and the extraction volume was 2 mL. The samples were centrifuged and the supernatant was measured for its absorbance in an ultraviolet spectrophotometer. The formula X=(C0-C) / C0×100%, where X is the degradation rate of tetracycline, C0 is the initial concentration of tetracycline, and C is the concentration of tetracycline after degradation.

[0064] Photo-Fenton degradation test: Prepare 100 mL of 20 mg / L tetracycline solution, and weigh 10 mg of 5%-FCN / TiO2 photo-Fenton catalyst prepared in Implementation Regulation 3. Adjust the tetracycline solution to pH 1, 3, 5, 7, and 9, then add the catalyst to the tetracycline solution in sequence and put it into the reaction device.

[0065] like Figure 8 As shown, Figure 8The FTIR images of the photo-Fenton catalysts prepared in Examples 1 to 5 of the present invention are compared with the peak position of carbon nitride in the Fourier spectrum of pure g-C3N4 nanosheets. It is found that the peak position of the g-C3N4 nanosheets in the FCN / TiO2 composite catalyst material has almost no change, indicating that the layer structure of the g-C3N4 nanosheets is not damaged after loading with Fe2O3. The peak is at 1200cm -1 ~1600cm -1 The fingerprint region between 3300cm and 400cm is caused by the stretching vibration of CN and C=N bonds. -1 ~3400cm -1 The broad peaks in the range of 500 cm-1 are attributed to the stretching vibrations of NH and OH bonds. -1 ~700cm -1 The vibration peaks at the positions are attributed to the Ti-O-Ti bonds, proving the formation of FCN / TiO2 composite catalytic materials.

[0066] like Fig. 9 As shown, Fig. 9 The degradation rate-time curve of tetracycline hydrochloride degradation under visible light by the photo-Fenton catalyst prepared in Examples 1 to 5 of the present invention; Figure 4 The results show that the degradation performance of tetracycline hydrochloride by g-C3N4 photo-Fenton catalytic materials loaded with different Fe2O3 mass ratios is different. Among them, 5%-FCN / TiO2 has the strongest degradation effect on tetracycline within 120 minutes, reaching about 91%, which effectively improves the photocatalytic degradation effect of pure g-C3N4. The loading amount of 5%-FCN / TiO2 is optimal, and the nanosheet-shaped Fe2O3 is evenly distributed on carbon nitride, which makes the g-C3N4 nanosheets have strong light response ability and promotes the generation and migration of photogenerated electrons.

[0067] like Fig.10 As shown, Fig.10 This is a diagram showing the catalytic degradation of tetracycline hydrochloride solution at different pH values ​​by the 5%-FCN / TiO2 photo-Fenton catalyst prepared in Example 3 of the present invention. Figure 5 It shows that different pH has a certain effect on the adsorption performance of the composite material. The degradation efficiency of 5% FCN / TiO2 under acidic conditions is slightly better than that under alkaline and neutral conditions. Among them, the degradation efficiency of tetracycline hydrochloride reaches a maximum of 92.6% at pH=3. The reason is that under acidic conditions, H +It is conducive to the process of O2 gaining electrons at the cathode to generate H2O2, which in turn promotes the generation of strong oxidizing substances such as OH in the system, thereby greatly improving the catalytic degradation effect. As the pH value increases, the catalytic activity gradually decreases. This is because too high a pH value inhibits the generation of H2O2. However, when the pH value in the solution is too low (pH = 1), the degradation efficiency of tetracycline hydrochloride is the lowest. This may be due to the interaction between H2O2 and the abundant H + Combine to form H3O2 + , reducing the H2O2 and Fe 2+ The reaction leads to a decrease in the amount of ·OH generated and a decrease in catalytic activity. Overall, the degradation efficiency only dropped from 92.6% to 75% when the pH increased from 3 to 9, indicating that the composite material has a wide range of pH applications in this system and is not limited to acidic or weakly acidic conditions, which overcomes the disadvantage of the traditional Fenton reaction with high pH requirements.

[0068] In order to further improve the degradation efficiency of TC, this experiment studied the effect of different bias voltages on the degradation efficiency of TC. This experiment adopted the controlled variable method, applying different voltages of 0.5V, 1.0V, 1.5V and 2.0V to the system. The anode material was 5%-FCN / TiO2 photo-Fenton catalyst, the cathode material was carbon sheet, and other experimental conditions remained unchanged. Fig.11 As shown, Fig.11 This is a graph showing the degradation efficiency of TC of a tetracycline hydrochloride solution at different bias voltages using a 5%-FCN / TiO2 photo-Fenton catalyst prepared in Example 3 of the present invention. Fig.11 It can be seen that as the applied bias voltage gradually increases, the degradation efficiency of TC gradually increases. When the applied bias voltage is 1.5V, the degradation efficiency of TC by 5%FCN / TiO2 reaches the maximum, reaching 91% at 180 min, because applying an appropriate bias voltage can promote the separation of electron-hole pairs in the composite electrode material to achieve the best separation ability, reduce their recombination, and thus improve the degradation efficiency of TC; however, when the applied voltage is too large, the degradation efficiency of TC decreases instead, because the violent decomposition of water produces too many active species, causing the degradation intermediates to adhere to the electrode surface, which hinders the contact between the pollutant molecules and the reactive active sites on the photoelectrode, affecting the next reaction, and reducing the degradation efficiency of TC.

[0069] In summary, the present invention obtains a composite material with better photo-Fenton catalytic activity by controlling the amount of FeCl3·6H2O added. The Fe2O3-loaded g-C3N4 photo-Fenton catalytic material with the (110) face as the dominant crystal face has a good adsorption and decomposition effect on H2O2. The temperature required for the hydrothermal reaction of the present invention is only 170-180°C, and the energy consumption is low. On the other hand, the reagents used in the preparation process, such as water, ethanol and chloride, are easy to obtain and do not pollute the environment.

[0070] The g-C3N4 nanosheets prepared by the method of the present invention have a larger specific surface area than Bulk-g-C3N4 and can produce more reactive active sites; the introduction of Fe2O3 in the catalytic material shortens the band gap of g-C3N4, reduces the resistance of photogenerated electron transmission, promotes the separation and migration of photogenerated carriers, and is beneficial to improving the photo-Fenton degradation efficiency of the catalyst. The degradation activity test under visible light shows that the g-C3N4 photo-Fenton catalytic material loaded with Fe2O3 on the dominant crystal surface prepared by the present invention has good stability and sustainability, and has a better degradation effect than g-C3N4 nanosheets.

[0071] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A photo-Fenton catalytic material, characterized in that: Obtained from the following components: A carbon substrate having a TiO2 nanowire array disposed thereon; Modified carbon nitride, the modified carbon nitride comprises carbon nitride and Fe2O3 quantum dots supported on the carbon nitride.

2. The photo-Fenton catalytic material according to claim 1, characterized in that: The mass percentage of the Fe2O3 quantum dots on the carbon nitride is 1wt%~9wt%.

3. The photo-Fenton catalytic material according to claim 1, characterized in that: The carbon nitride is porous carbon nitride; The carbon substrate is graphite felt, carbon cloth or activated carbon.

4. The method for preparing the photo-Fenton catalytic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: A carbon substrate provided with a TiO2 nanowire array is subjected to a deposition reaction in a modified carbon nitride solution to obtain a photo-Fenton catalytic material.

5. The method for preparing the photo-Fenton catalytic material according to claim 4, characterized in that: The carbon substrate provided with the TiO2 nanowire array is electrophoretically deposited in an acetone solution of modified carbon nitride under the action of iodine; The usage ratio of the iodine element, modified carbon nitride and acetone is: (18-22) mg: (8-12) mg: (25-35) mL.

6. The method for preparing the photo-Fenton catalytic material according to claim 4, characterized in that: The modified carbon nitride is prepared by the following method: Carbon nitride, FeCl3·6H2O and NH4HCO3 are mixed and stirred for 10 h to 14 h, and the material obtained after the mixing and stirring is calcined at 340°C to 360°C for 1.5 h to 2.5 h to obtain modified carbon nitride.

7. The method for preparing the photo-Fenton catalytic material according to claim 6, characterized in that: The carbon nitride is porous carbon nitride, which is prepared by the following method: Melamine and cyanuric acid in a mass ratio of 1: (1-1.2) are stirred in a solvent for 10-14 hours, and filtered to obtain a precipitate after standing. The precipitate is calcined at 500-550° C. for 3-5 hours to obtain porous carbon nitride.

8. Use of the photo-Fenton catalytic material described in any one of claims 1 to 3 or the photo-Fenton catalytic material obtained by the preparation method described in any one of claims 4 to 7 in the preparation of an antibiotic wastewater degradation agent.

9. A method for degrading antibiotic wastewater, characterized in that: The following steps are involved: S1) adsorbing an antibiotic wastewater degradation agent in antibiotic wastewater in the absence of light to obtain dark-field adsorbed wastewater; the antibiotic wastewater degradation agent is the photo-Fenton catalytic material described in any one of claims 1 to 3 or the photo-Fenton catalytic material obtained by the preparation method described in any one of claims 4 to 7; S2) Under light conditions, the oxidant is reacted with the dark field adsorption wastewater obtained in step S1).

10. The method for degrading antibiotic wastewater according to claim 9, characterized in that: In step S1), the pH of the antibiotic wastewater is 2-9.